2008
DOI: 10.2174/187152808785107651
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Therapy in Dermatologic Disorders

Abstract: Intravenous immunoglobulin (IVIG) is sterilized and purified human plasma which contains supra-physiologic levels of immunoglobulin G. IVIG is currently used in the treatment of immunodeficiency syndromes, inflammatory disorders and infectious diseases. Although numerous immunomodulatory mechanisms have been suggested, the exact mechanisms of action are poorly understood. There is also accumulating evidence that high-dose IVIG is efficacious in the treatment of some skin diseases, despite the lack of evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Sporadic case reports, as well as prospective and retrospective, multicenter studies have shown that early administration of high-dose IVIG helped to halt the progression of disease and reduce fatality. 522 Most reported patients were treated with IVIG in conjunction with other drugs, such as corticosteroids. A more recent and relatively large-scale (65 patients), retrospective study of IVIG (in addition to corticosteroids) in these disorders also showed a trend toward earlier resolution and reduced mortality, although results were not statistically significant.…”
Section: Nonatopic Dermatologic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic case reports, as well as prospective and retrospective, multicenter studies have shown that early administration of high-dose IVIG helped to halt the progression of disease and reduce fatality. 522 Most reported patients were treated with IVIG in conjunction with other drugs, such as corticosteroids. A more recent and relatively large-scale (65 patients), retrospective study of IVIG (in addition to corticosteroids) in these disorders also showed a trend toward earlier resolution and reduced mortality, although results were not statistically significant.…”
Section: Nonatopic Dermatologic Disordersmentioning
confidence: 99%
“…Case reports suggesting improvement with IVIG exist in these additional disorders affecting the skin not covered elsewhere in this review: psoriasis, pyoderma gangrenosum, pretibial myxedema, and Mucha-Habermann disease. 522 More recent reports also include dystrophic calcinosis cutis 525 and scleromyxedema. 526 Other organ-specific diseases Cardiac disease.…”
Section: Nonatopic Dermatologic Disordersmentioning
confidence: 99%